SOSIALISASI PEMAHAMAN PERATURAN PERMAINAN BOLA VOLI PADA ATLET KELOMPOK USIA 16 TAHUN - Indrayogi Indra; Riza Sukma Fauzi; Rudi; Udi Sahudi; Novi Syahfitri Supriatna (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
This dedication is motivated by the fact that there are still many athletes in the 16 year old age group in Sumedang Regency who do not understand the rules of volleyball games against the rules of volleyball games. This service aims to socialize the level of understanding of volleyball game rules for athletes in the 16 year old group in Sumedang Regency. The method of implementing community service, based on the stages: (1) preparation stage, (2) implementation stage, (3) evaluation stage, and (4) expected result stage. Providing socialization materials regarding the latest volleyball game rules from the FIVB. The samples taken were all female athletes in the 16 year age group, totaling 112 athletes from 8 clubs that were registered in Sumedang Regency. The results obtained are increasing understanding of volleyball game rules in athletes aged 16 years.